Microporous carbon monolith synthesis and production for methane storage - Tash, T.A. (2017)
The synthesis, characterization, and performance of a new low pressure, monolithic, activated carbon adsorbent developed for methane storage is discussed and compared to other adsorbents. The effect of particle packing density on the storage capacity of tanks filled with commercially available and developmental adsorbents is quantified. 20 kg of the developed monolithic material is tested using a custom built, 40 L, space conformable tank test assembly. The performance is found to be superior to metal organic frameworks and other activated carbons reported in literature based on high tank volumetric and gravimetric storage capacities. The developed material has a pore structure and external dimensions that allow for rapid adsorption/desorption with gas being able to reach the center of the 40 L tank within ∼3 s. The developed material delivers 151 V/V of methane between 35 bar and 1 bar in the 40 L tank. A continuous discharge flow rate of 2 g/s at 5 bar for a 10 gge system was demonstrated.